Value Orientations and Institutional Trust as Contributors to the Adoption of Online Services in Youth: A Cross-Country Comparison - Lep, Žan; Trunk, Aleš; Babnik, Katarina (Frontiers in Psychology, 2022)
Internet usage data from around the globe show that adolescents are the most frequent internet users, but mostly for leisure activities and maintaining social contacts. In the present study, we focused on internet use for e-services, which could improve youth efficiency in the financial domain (responsible consumer behaviour) and bridge the online divide in youth. Specifically, we explored how societal constructs (namely institutional trust and personal values) influence the use of the internet for online shopping, e-banking and communication with providers of goods and services online. We used a representative sample of adolescents (N = 10.902) from 10 countries of Southeast Europe where a great variability in internet use is present, and where the use of e-services is generally lower than the EU average. This also allowed for meaningful cross-country comparisons. We tested a structural equation model of values predicting the use of the internet through institutional trust (including some relevant demographic variables such as settlement size, SES, internet use frequency) which was grounded in social capital theory, cultural theory, and Schwartz human values model. The model exhibited a good fit to the data but the strengths of regressional paths were rather modest. Looking into the cross-country stability of the model, however, revealed some notable differences: while the relationship between trust and use of the internet for e-services was modest in some countries, the relationship was insignificant in other countries, where internet usage is lower in general. This suggests that strategies aimed at leveraging e-services and digital technology potential in youth should also account for cultural specificities in the transitional economies and cultural settings with sub-optimal adoption of digital services.